2008
DOI: 10.1007/s12036-008-0016-z
|View full text |Cite
|
Sign up to set email alerts
|

X-ray emission from solar flares

Abstract: Solar X-ray Spectrometer (SOXS), the first space-borne solar astronomy experiment of India was designed to improve our current understanding of X-ray emission from the Sun in general and solar flares in particular. SOXS mission is composed of two solid state detectors, viz., Si and CZT semiconductors capable of observing the full disk Sun in X-ray energy range of 4-56 keV. The X-ray spectra of solar flares obtained by the Si detector in the 4-25 keV range show evidence of Fe and Fe/Ni line emission and multi-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Thus to calculate the peak plasma temperature and the DEM we have employed the least- 2 fitting to the SOXS X-ray spectra in OSPEX as described earlier by Jain et al (2008).…”
Section: Spectra Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Thus to calculate the peak plasma temperature and the DEM we have employed the least- 2 fitting to the SOXS X-ray spectra in OSPEX as described earlier by Jain et al (2008).…”
Section: Spectra Analysismentioning
confidence: 99%
“…Thus it is extremely important to characterize the soft X-ray emission below 10 keV. Further, the X-ray emission between 10 and 25 keV should in principle include both thermal and non-thermal contributions (Aschwanden, 2007;Jain et al, 2008). Therefore, the characterization of flare plasma up to 25 keV with high spectral resolution observations becomes further important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3. We analysed 2-5 spectra depending on the duration of each microflare under study and found that the best fit to the spectra is by thermal for energy range 4-8 keV, while the continuum of the spectra at energies > 8 keV fits well by broken power-law (Jain et al 2008). This result shows that the microflares are most likely the product of both mechanism viz., thermal and non-thermal, which is an indicator of hybrid mechanism in microflares as proposed earlier by Jain et al (2006b).…”
Section: Discussionmentioning
confidence: 82%
“…The SOXS provides solar flare observations in X-ray waveband in the energy range of 4-56 keV. [27][28][29][30].…”
Section: Selection Criteria and Datamentioning
confidence: 99%